Peran Penyuluh Agama Islam dalam Pencegahan Stunting: Studi Kasus di Desa Sukorejo Wonogiri - Supriyanto (CV Omah Kreator, 2025)
Stunting remains one of the major chronic nutritional problems and a persistent public health challenge in Indonesia, particularly in rural areas. Efforts to prevent stunting require not only medical interventions but also social and religious approaches that foster community awareness. This study aims to analyze the role of Islamic religious instructors in preventing stunting in Sukorejo Village, Puhpelem District, Wonogiri Regency, and to identify the supporting and inhibiting factors in their implementation. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation, and analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings indicate that Islamic religious instructors play an educational role through majelis taklim and religious counseling activities that emphasize the importance of nutrition, hygiene, and Islamic-based parenting as part of religious obligations. The main supporting factors include well-educated instructors, institutional support from the Office of Religious Affairs (KUA) and the village government, and collaboration with community health centers and posyandu cadres. The inhibiting factors consist of limited time for counseling activities, low participation rates among congregants, and generally low educational levels within the community. This study contributes to the literature on health-oriented dakwah and demonstrates that Islamic religious instructors hold strategic potential in supporting the national program for stunting prevention through Islamic values and community moral education.